Cross-border nursing education: questions, qualms and quality assurance. Issue 2 (11th March 2019) - Naidoo, Vasanthrie; Sibiya, Maureen Nokuthula
Abstract : Purpose: The purpose of this paper is to share insights, research findings and discuss key issues relating to quality practices and quality assurance in cross-border nursing education program development and implementation. Design/methodology/approach: The authors used a qualitative, multiple case-study approach, by sampling local, national and international nursing education institutions, academia and nurse graduates to identify challenges and best operating practices in implementing and facilitating cross-border education. Findings: The authors reveal that quality assurance affects cross-border nursing education program design, delivery and implementation. Research limitations/implications: Quality assurance plays an important role in cross-border nursing education, by enhancing the reputation and recognizing the effectiveness and capacity of the educational institution. These findings of this study can offer valuable insight to forthcoming as well as existing nursing education curriculum developers who plan to engage in national or international educational partnerships. Practical implications: Quality assurance plays an important role in cross-border nursing education, by enhancing the reputation and recognizing the educational institution's effectiveness and capacity. The findings offer valuable insight into forthcoming and existing nursing education for curriculum developers who plan to engage in national or international educational partnerships. Originality/value: This paper explores inherent challenges in cross-border nursing education and maximized data collection opportunities by sampling participants from both national and international settings.